Penerapan Pembelajaran Mozaik Menggunakan Kulit Telur Dalam Meningkatkan Motorik Halus Pada Anak Usia 4-5 Tahun Di PAUD Asya’iriyah - sari , Dewanti Marlia; Choiriyah, Choiriyah; Anggraeni , Rita Intan (CV. ITTC INDONESIA, 2024)
The aim of this research is to improve fine motor skills through the application of mosaic learning using egg shells to improve fine motor skills in children aged 4-5 years at Asya'Iriyah preschool. This research was carried out in 2 cycles using the Classroom Action Research (PTK) methodology carried out by teachers and researchers. There were 10 students who were research subjects. The research subjects were children aged 4 - 5 years. The instrument used was a child activity observation sheet. This research uses the Kemmis and Mc Taggart research model. The indicator of success in this research is if the child's creativity has reached a minimum of 80%. The development of fine motor skills through mosaic activities using egg shells in children aged 4 - 5 years at Asya'iriyah Preschool increases with each cycle. Based on the increase in cycle I, it increased by 30% and cycle II increased by 60% and this research stated that mosaic learning activities can improve fine motor skills in children aged 4 - 5 years at Asya'iriyah Early Childhood Education.